Pengembangan Objek Wisata Pantai dalam Meningkatkan Taraf Hidup Masyarakat di Kabupaten Batu Bara - Hardiman Sihombing; Humaizi; Harmona Daulay (PERSPEKTIF, 2023)
The aim of this research is to analyze the strategy of the Paris, Youth and Sports Center in increasing travel visits to the Western Cape and factors of slavery and influence that affect the development of coastal travel objects in increasing the standard of living in the Western Cape. The method used in this study is qualitative with data collection techniques of library studies. As for the discovery of this research, the strategy of the Pariwisata, Youth and Sports Center in increasing the travel visit to the Western Cape is not yet maximum, can be seen from visits to the Western Cape is still very low. In 2010 there were 345,311 tourists, in 2011 there were 311,777, in 2012 there were 325,063, in 2013 there were 335,295, in 2014 there were 348,765, and in 2015 there were 285,824. That's a very low number, considering the West Bank is an area with lots of different travel objects. Factors that hinder the development of coastal travel objects in increasing the standard of living in the Western Cape Town, namely that the policies of the Western Cape Town government have not yet damaged the development programme of society, not just as much as the sovereignty of public art, but the development of the creative economy of society, - so that opportunities can be created to work and work in society. Another factor is that the facilities around the beach are unsuitable and not maximum to extend the facilities that should be in the tourist area.